Construction of an overexpression library for Mycobacterium tuberculosis. Issue 1 (20th August 2018) - Melief, Eduard; Kokoczka, Rachel; Files, Megan; Bailey, Mai Ann; Alling, Torey; Li, Hongye; Ahn, James; Misquith, Ayesha; Korkegian, Aaron; Roberts, David; Sacchettini, James; Parish, Tanya
Abstract: There is a pressing need to develop novel anti-tubercular drugs. High-throughput phenotypic screening yields chemical series that inhibit bacterial growth. Target identification for such series is challenging, but necessary for optimization of target engagement and the development of series into clinical drugs. We constructed a library of recombinant Mycobacterium tuberculosis strains each expressing a single protein from an inducible promoter as a tool for target identification. The library of 1733 clones was arrayed in 96-well plates for rapid screening and monitoring growth. The library contains the majority of the annotated essential genes as well as genes involved in cell wall and fatty acid biosynthesis, virulence factors, regulatory proteins, efflux, and respiration pathways. We evaluated the growth kinetics and plasmid stability over three passages for each clone in the library. We determined expression levels (mRNA and/or protein) in 396 selected clones. We screened the entire library and identified the Alr-expressing clone as the only recombinant strain, which grew in the presence of d -cycloserine (DCS). We confirmed that the Alr-expressing clone was resistant to DCS (7-fold shift in minimum inhibitory concentration). The library represents a new tool that can be used to screen for compound resistance and other phenotypes.